A Novel Pectic Polysaccharide of Jujube Pomace: Structural Analysis and Intracellular Antioxidant Activities - Ximeng Lin; Keshan Liu; Sheng Yin; Yimin Qin; Peili Shen; Qiang Peng (MDPI AG, 2020)
After extraction from jujube pomace and purification by two columns (DEAE-Sepharose Fast Flow and Sepharcyl S-300), the structure of SAZMP4 was investigated by HPGPC, GC, FI-IR, GC-MS, NMR, SEM, and AFM. Analysis determined that SAZMP4 (Mw = 28.94 kDa) was a pectic polysaccharide mainly containing 1,4-linked GalA (93.48%) with side chains of 1,2,4-linked Rha and 1,3,5-linked Ara and terminals of 1-linked Rha and 1-linked Ara, which might be the homogalacturonan (HG) type with side chains of the RG-I type, corresponding to the results of NMR. In AFM and SEM images, self-assembly and aggregation of SAZMP4 were respectively observed indicating its structural features. The antioxidant activity of SAZMP4 against H2O2-induced oxidative stress in Caco-2 cells was determined by activity of superoxide dismutase (SOD) and glutathione peroxidase (GSH-Px) as well as malondialdehyde (MDA) and reactive oxygen species (ROS) levels, indicating SAZMP4 can be a natural antioxidant. Also, a better water retention capacity and thermal stability of SAZMP4 was observed based on DSC analysis, which could be applied in food industry as an additive.